Penguatan Literasi Lingkungan Anak Melalui Edukasi Interaktif Deforestasi Di Desa Puraseda, Kabupaten Bogor - Surfian Rahmat; Faris Widyatmoko; Ahmad Prasetya Hadi; Rafly Putra Gibrani; Muhammad Mahdy Nasrullah Perkasa (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Deforestation in the Bogor region, including the area surrounding Puraseda Village, Leuwiliang Subdistrict, continues to pose a serious threat to environmental sustainability and the livelihood of communities living near the forest, while also hindering progress toward the Sustainable Development Goals (SDGs), particularly Goal 4 (Quality Education), Goal 13 (Climate Action), and Goal 15 (Life on Land). Low environmental literacy among children is one factor that slows sustainable forest conservation efforts, as children are the next generation who play an important role in preserving nature in the future. This community service program aims to strengthen the environmental literacy of elementary school-age children in Puraseda Village through interactive education on the theme of deforestation, as a concrete contribution to advancing the SDGs agenda at the village level. The implementation method consists of a preparation stage, an educational stage using storytelling, educational games, animated video screenings, question-and-answer sessions, and forest poster coloring, followed by an evaluation using pretest and posttest questionnaires. The results show an improvement in participants' understanding of the causes, impacts, and prevention efforts related to deforestation, as well as high enthusiasm throughout the educational process. This program is expected to serve as an SDGs-based model of environmental education that can be replicated in other villages around the Bogor forest area to foster ecological awareness from an early age while supporting sustainable development at the local level.